Injectable, adhesive, and ROS-responsive hydrogel loaded with curcumin and bFGF for enhanced oral ulcer healing - Yaru Zhang; Zengqi Ye; Chenhui Chen; Jiancheng Yu; Yihao Wu; Ziqi Yu; Yue Huang; Yangshuai Jin; Xian Tong; Li Zhu; Jixing Lin; Xiaojun Cai; et al. (Chemical Engineering Journal, 2026)

Functional Validation of the Phase I–II–III Detoxification Pathway in Azumapecten farreri using Optimized RNA Interference Technology - Limin Lu; Guanchao Zheng; Yichen Lin; Chenfan Dong; Jixing Peng; Haiyan Wu; Zhijun Tan (Marine Biotechnology, 2026)

Amino Acid Metabolic Remodeling in Bivalves Under Environmental Stress: Roles, Mechanisms, and Implications for Bivalve Health—A Review - Yichen Lin; Wei Chen; Jixing Peng; Xinnan Zhao; Yan Di; Mengmeng Guo; Yanfang Zhao; Haiyan Wu; Guanchao Zheng; Qianqian Geng; Zhijun Tan (Fishes, 2026)
Climate change and increasing instability in coastal marine environments have intensified stressors such as elevated temperature, hypoxia, salinity variation, and pollutant exposure, posing major challenges to the survival, health, and culture performance of bivalves. As economically important aquaculture species and key components of coastal ecosystems, bivalves are highly sensitive to environmental fluctuations, making their metabolic responses highly relevant to both physiological adaptation and aquaculture sustainability. Increasing evidence indicates that metabolic remodeling is an important adaptive strategy supporting bivalve tolerance to environmental stress, with amino acid metabolic remodeling emerging as one of its most sensitive and functionally important components. This review summarizes the major response patterns, key pathways, and potential regulatory mechanisms of amino acid metabolism in bivalves under different stress conditions. Different environmental stressors induce distinct yet integrated shifts in amino acid metabolism, including enhanced catabolism, carbon–nitrogen redistribution, osmotic regulation, and antioxidant defense, thereby supporting energy homeostasis and physiological stress tolerance in bivalves. By highlighting amino acid metabolic remodeling as a central mechanism of bivalve adaptation to environmental stress, this review provides insights into adaptive responses, metabolite-based indicators for monitoring aquaculture environments and bivalve health, and management strategies for improving resilience in bivalve aquaculture.

Biodegradable Mg-Sr-Zr-Ho alloy with multifunctional angiogenic, antibacterial, anti-inflammatory, and osteogenic properties for orthopedic fixation - Xian Tong; Qi Li; Yuxin Zhang; Yuncang Li; Chi Yang; Jixing Lin; Cuie Wen; Jisi Zheng; Yusen Dai (Chemical Engineering Journal, 2026)

Spatiotemporal evolution and influencing factors of soil erosion sensitivity in the red soil region of Southern China - Jinhuang Lin; Jixing Huang; Weihan Zhu; Yongwu Dai; Yan Huang; Xiaoyan Yan; Fangfang Zou; Youquan Ouyang (Journal of Mountain Science, 2026)

A dynamic dissolution non-equilibrium mass transfer model for simulating CO2 migration in groundwater and its application in CO2-EOR project - Jixing Wang; Yang Li; Qianguo Lin (Journal of Cleaner Production, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

Comprehensive quality evaluation and principal component analysis of Crassostrea gigas from North Yellow Sea, China: characterizing nutritional, flavor, and functional profiles - Shanqin Huo; Jixing Peng; Xinnan Zhao; Yichen Lin; Xudong Li; Zhijun Tan (Journal of Oceanology and Limnology, 2026)

Implicit Difference Solution for One-Dimensional Consolidation of Unsaturated Soil: Numerical Verification and Application to Soil-Cushion System - Qian He; Quan Yuan; Lin Lang; Jixing Cao (Mathematical Geosciences, 2025)

In vitro and in vivo studies of a biodegradable Zn-4Ag-0.1Sc alloy with high strength-elongation product, cytocompatibility, osteogenic differentiation, and anti-infection properties for guided bone-regeneration membrane applications - Xian Tong; Xinkun Shen; Zhiqiang Lin; Lei Lu; Khurram Munir; Runqi Zhou; Li Zhu; Yuncang Li; Jianfeng Ma; Cuie Wen; Jixing Lin (Chemical Engineering Journal, 2024)

Metabolites and metabolic pathway analysis of sulfadimidine in carp (Cyprinus carpio) based on UHPLC-Q-orbitrap HRMS - Shuwen Wang; Lihong Xing; Xiaojie Sun; Zhaoxin Li; Tao Ding; Jiyao Wang; Jixing Peng; Haijian Ma; Ting Lin; Qingli Yang (Environmental Research, 2024)

Antiadhesive, antibacterial, and anti-inflammatory sandwich-structured ZIF8-containing gauze for enhanced wound healing - Xinghai Wu; Cheng Wang; Jia Wang; Yuchen Feng; Yunpeng Zhu; Yijia Pan; Yifan Yuan; Chenhui Chen; Junyan Cao; Jixing Lin; Xian Tong; Yuncang Li; et al. (Chemical Engineering Journal, 2024)

Projections of climate-driven biogeographical changes of benthic mollusks in the Yellow Sea and East China Sea - Yong Xu; Lin Ma; Jixing Sui; Xinzheng Li; Hongfa Wang; Baolin Zhang (Marine Environmental Research, 2024)

Lake regime shift from submerged macrophyte to phytoplankton affected phosphorus speciation in sediment and eutrophic state in Caohai Lake, Guizhou, China - Jixing Dong; Yanmin Guo; Pinhua Xia; Yuanbin Tian; Feifei Zheng; Anyan Li; Tao Lin; Ruiwen Li (Journal of Oceanology and Limnology, 2023)

Potential impacts of climate change on the distribution of echinoderms in the Yellow Sea and East China Sea - Yong Xu; Lin Ma; Jixing Sui; Xinzheng Li; Hongfa Wang; Baolin Zhang (Marine Pollution Bulletin, 2023)

Super-tough and self-healable all-cellulose-based electrolyte for fast degradable quasi-solid-state supercapacitor - Xiaobo Lin; Mengying Wang; Junchai Zhao; Xiangfeng Wu; Jixing Xie; Jinhui Yang (Carbohydrate Polymers, 2023)

Report of epibenthic macrofauna found from Haima cold seeps and adjacent deep-sea habitats, South China Sea - Dong Dong; Xinzheng Li; Mei Yang; Lin Gong; Yang Li; Jixing Sui; Zhibin Gan; Qi Kou; Ning Xiao; Junlong Zhang (Marine Life Science & Technology, 2021)
This work reports on a preliminary taxonomic study of epibenthic macroinvertebrates collected or observed by underwater video at the Haima cold seeps and in adjacent deep-sea habitats, including a mud volcano field and Ganquan Plateau, during an expedition in the South China Sea by the Chinese-manned submersible Shenhai Yongshi in May 2018. A total of 41 species belonging to 6 phyla were identified, among which 34 species were collected from the Haima cold seeps. Mollusks and crustaceans that are specialized in reducing habitats were predominant in biotopes of the Haima cold seeps, whereas sponges and cold-water corals and their commensals were prominent in communities of the mud volcano field and the slopes of Ganquan Plateau. The distribution and faunal composition of each taxonomic group are discussed.

Effects of topographic factors and aboveground vegetation carbon stocks on soil organic carbon in Moso bamboo forests - Huiyun Fang; Biyong Ji; Xu Deng; Jiayang Ying; Guomo Zhou; Yongjun Shi; Lin Xu; Jixing Tao; Yufeng Zhou; Chong Li; Hao Zheng (Plant and Soil, 2018)